Auditory speed tasks as potential candidates for the study of cognitive ageing. Issue 2 (4th March 2018) - Zajac, Ian T.; Nettelbeck, Ted
ABSTRACT: Speed of information processing is an important cognitive ability. It facilitates the efficient operation of higher order cognitive functions, such as reasoning, and is implicated in various models of cognitive decline. The present study considers the potential benefits of expanding the measurement of processing speed to include the auditory modality. It examines the reliability and factorial structure of a variety of auditory and visual speed tasks in a sample of N  = 138 older adults aged between 51 and 82 years. Our findings demonstrate that auditory measures can be used to assess processing speed as indexed by existing widely used tests of this ability. Moreover, the inclusion of auditory tasks significantly increases the relationship between processing speed and general cognitive ability. This novel research provides strong evidence of the suitability of auditory speed tasks for the study of cognitive function in older people, and demonstrates the importance of expanding cognitive measurement to include alternate modalities.